Бред сивого кобеля - Вильмонт Екатерина Николаевна (Про жизнь и про любовь, 2015)
Экземпляры: Ф. 12 (20191219) / Инвентарный номер: 45430 / Цена: 108.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: В 46 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6